Evaluation of the analgesic effect of ɑ-lipoic acid in treating pain disorders: A systematic review and meta-analysis of randomized controlled trials. (March 2022) - Cassanego, Gabriela; Rodrigues, Patrícia; De Freitas Bauermann, Liliane; Trevisan, Gabriela
Abstract: Neuropathic pain is the most prevalent form of chronic pain caused by a disease of the nervous system, such as diabetic polyneuropathy. ɑ-Lipoic acid (ALA) is an antioxidant that has been widely studied for the treatment of pain symptoms in diverse conditions. Therefore, this study aimed to investigate the efficacy of ALA in the treatment of different types of pain through a systematic review and meta-analysis of randomized clinical trials. The study protocol was registered in the International Prospective Registry of Systematic Reviews (CRD42021261971). A search of the databases resulted in 1154 articles, 16 of which were included in the review (9 studies with diabetic polyneuropathy and 7 studies with other painful conditions). Most of the included studies had a low risk of bias. ALA showed efficacy for the treatment of headache, carpal tunnel syndrome and burning mouth syndrome. Meta-analysis was conducted only with the studies using diabetic polyneuropathy. Compared to placebo, ALA treatment decreased the total symptom score (TSS). The subgroup meta-analysis indicated a decrease of stabbing pain, burning, paraesthesia, and numbness in ALA-treated patients compared to placebo. In addition, both routes of administration, intravenous and oral, demonstrated the efficacy to reduce TSS. Therefore, ALA should be used to treat diabetic polyneuropathy pain symptoms. However, the standardization of treatment time and the dose may advance for the approval of ALA for clinical use in diabetic polyneuroneuropathy. Graphical Abstract: ga1 Highlights: ɑ-Lipoic acid treatment decreased pain symptoms of migraine, carpal tunnel syndrome, and burning mouth syndrome. Diabetic polyneuropathy patients treated with ɑ-lipoic acid presented a reduction of the pain symptoms. Meta-analysis showed a decrease in the total TSS, NIS, NIS (LL) and NDS in diabetic polyneuropathy patients treated with ɑ-lipoic acid. Both ɑ-lipoic acid routes of administration, oral and intravenous, were effective to reduced TSS.